A new type connection with optimum stiffness configuration for very large floating platforms. (August 2022) - Lu, Ye; Zhang, Haicheng; Chen, Yuchao; Shi, Qijia; Zhou, Ye
A novel connection for super-scale modularized floating platforms is put forward for the purposes of suppressing the oscillation of the platform. The platform consists of multiple blocks where semi-submergible modules are flexibly connected with upper decks by elastic cushions. For the connection between adjacent blocks, neighboring decks are linked by rigid hinges and neighboring floating modules are connected by flexible linkages. Based on the linear wave theory and rigid-module-flexible-connection (RMFC) model, the governing equation of motions for the modularized floating platform is derived by using a network modeling method. In numerical case studies, a five-block platform is investigated. Taking combined responses of the platform and the connector loads as an objective function, the stiffness configuration of the connection and the elastic cushion is optimally determined by using a genetic algorithm. At last, the short-term extreme responses of the floating platform with the optimum setting of the stiffness configuration of the connection are analyzed.